Examining Recovery Status and Supports before and after Substance Abuse Disorder Treatment Among Clients Who Experienced Lifetime and Recent Firearm-Related Threats. (July 2022) - Logan, TK; Cole, Jennifer; Schroeder, Maggie
Firearm-related risks have often been overlooked in the sequela of substance use and substance use disorders. This study compares adult substance abuse disorder treatment (SADT) clients who experienced recent ( n = 274) and lifetime ( n = 889) firearm threats to adults who were not threatened with a firearm ( n = 2029) before and 12 months after program entry. More men experienced firearm threats (38.8%) than women (34.2%). However, among those with any firearm threats, more women (27.2%) experienced firearm threats in the year before program entry than men (20.2%). Being threatened with a firearm was associated with increased economic vulnerability, criminal justice system involvement, mental health problems, and victimization both before and after SADT program entry. A higher number of adverse childhood experiences were associated with firearm threats and particularly recent firearm threats. Results of this study underscore the importance of screening for firearm-related risks in substance abuse disorder treatment programs.